The agency of reformers in new European financial centres: A historically informed financial geography - Tom Hashimoto (Finance and Society, 2021)
While institutional frameworks are the dominant approach to analysing the geography of finance, this article focuses on how individual policymakers influence the characteristics of financial institutions and set, or even alter, financial centre development. The historical narratives from Central and Eastern Europe (CEE) that this article presents reveal post-socialist reformers' contrasting philosophies and approaches, despite their shared goals of market liberalisation and European integration. These reforms (or lack thereof) differentiated the securities markets in Warsaw, Prague, and Budapest, especially with respect to financial intermediary mechanisms. Although the legacies of such reforms continue to shape an uneven landscape of financial centres in CEE, this article proposes reformer-centred narratives as an alternative to deterministic institutional thinking. The article argues that historical narratives that foreground the actions and ideas of key policymakers need to be included in the observation framework of financial centre development, in a similar way to how scholars analyse foreign policy by focusing on the heads of governments and ministers.
Keywords: 300; Agency; policymakers; financial history; Central and Eastern Europe; financial centres